2020
DOI: 10.3390/agronomy10030320
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tillage Systems, and Forms and Rates of Nitrogen Fertilizers on CO2 and N2O Fluxes from Winter Wheat Cultivation in Oklahoma

Abstract: Cultivation of winter wheat under reduced tillage systems is increasing in the U.S. Southern Great Plains. Likewise, there is revived interest for including summer legumes in monocultures of winter wheat as green sources of nitrogen (N). This study investigated the influence of tillage systems (no- and conventional tillage), and source and rates of N fertilizer (0, 45 and 90 kg N ha−1 yr−1 in inorganic N fertilizer, and cowpea as green manure) on emissions of carbon dioxide (CO2) and nitrous oxide (N2O) from w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…In Southern Illinois, Kapusta et al (1996) also observed no difference in corn yield among CT, NT, and RT on a silt loam soil after 20 years under each tillage treatment. Moreover, similar GPP for wheat between CT and NT systems was recently reported in the inland Pacific Northwest region with a Mediterranean climate (Chi et al, 2016) and in the Southern Great Plains with a humid subtropical climate (Kandel et al, 2020) using the eddy covariance method.…”
Section: Impacts Of Tillage Management On Crop Gpp Et and Cwpsupporting
confidence: 78%
“…In Southern Illinois, Kapusta et al (1996) also observed no difference in corn yield among CT, NT, and RT on a silt loam soil after 20 years under each tillage treatment. Moreover, similar GPP for wheat between CT and NT systems was recently reported in the inland Pacific Northwest region with a Mediterranean climate (Chi et al, 2016) and in the Southern Great Plains with a humid subtropical climate (Kandel et al, 2020) using the eddy covariance method.…”
Section: Impacts Of Tillage Management On Crop Gpp Et and Cwpsupporting
confidence: 78%
“…More active fractions of organic C and N, enzyme activities, and associated microbial properties have been shown sensitive to tillage management in the region, including studies in the Central Rolling Prairies MLRA in Oklahoma (Kandel et al., 2020), in the Southern High Plains in Texas (Burke et al., 2019), in the Mississippi Blackland Prairie MLRA (Adeli et al., 2019), in the Southern Mississippi River Alluvium MLRA (Locke et al., 2013; Tyler, 2019), in the Southern Piedmont MLRA in Georgia (Franzluebbers & Stuedemann, 2015), in the Southern Blue Ridge MLRA in North Carolina (Wang et al., 2017), at multiple long‐term research station locations in North Carolina (Roper et al., 2017), and in multiple on‐farm fields in North Carolina (Franzluebbers, 2021). Curiously, in an earthworm preference study, a manure worm ( Eisenia fetida ) had no preference for soil under NT or with tillage when taken from a 4‐yr study in the Southern Mississippi River Alluvium in Arkansas (Bouldin et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Rajinder et al (2017) showed that split applications of nitrogen fertilizer may help to meet the nitrogen demand via soil supply and to enhance crop yield, grain quality, and fertilizer use efficiency. For this reason, appropriate split nitrogen applications are the most critical component of nitrogen fertilizer management ( Kandel, Gowda & Northup, 2020 ; Li et al, 2021 ). Previous studies have shown that pre-jointing nitrogen accumulation increased with an increase in the basal nitrogen rate, while post-jointing nitrogen accumulation increased with the increase in the topdressing nitrogen rate at a total fertilizer application rate of 210 kg/ha ( Shi et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%